2021
DOI: 10.3390/life11080752
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Types of Corticosteroids on Heart Rate Variability of Individuals with Duchenne Muscular Dystrophy—A Pilot Cross Sectional Study

Abstract: Individuals with Duchenne Muscular Dystrophy (DMD) have an impairment of cardiac autonomic function categorized by parasympathetic reduction and sympathetic predominance. The objective of this study was to assess the cardiac autonomic modulation of individuals with DMD undergoing therapy with Prednisone/Prednisolone and Deflazacort and compare with individuals with DMD without the use of these medications and a typically developed control group. Methods: A cross-sectional study was completed, wherein 40 boys w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Moreover, immunosuppressive agents could potentially affect autonomic function [ 37 ], thereby increasing the potential risk of arrhythmia, cardiac hypertrophy, and abnormal vascular remodeling [ 38 ]. Corticosteroids hold the potential to impact cardiovascular autonomic function, resulting in improved responses in terms of sympathovagal balance (Prednisone/Prednisolone), as observed in patients with Duchenne Muscular Dystrophy [ 39 ]. One study, using echocardiography techniques including Tissue Doppler imaging, found that before pyridostigmine intake, compared to controls, MG patients exhibited lower early diastolic AV-plane velocity and diminished peak systolic strain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, immunosuppressive agents could potentially affect autonomic function [ 37 ], thereby increasing the potential risk of arrhythmia, cardiac hypertrophy, and abnormal vascular remodeling [ 38 ]. Corticosteroids hold the potential to impact cardiovascular autonomic function, resulting in improved responses in terms of sympathovagal balance (Prednisone/Prednisolone), as observed in patients with Duchenne Muscular Dystrophy [ 39 ]. One study, using echocardiography techniques including Tissue Doppler imaging, found that before pyridostigmine intake, compared to controls, MG patients exhibited lower early diastolic AV-plane velocity and diminished peak systolic strain.…”
Section: Discussionmentioning
confidence: 99%
“…The non-linear analysis was performed using the Symbolic Dynamics Analysis method, with four indices [42], measured by grouping the patterns with 3 symbols into four types of clusters; the rate of occurrence for each pattern was defined as %0 V (no variation) reflecting only sympathetic modulation, %1 V (one variation) reflecting global variability by sympathetic and parasympathetic modulation, %2 LV (two like variations), and %2 UV (two unlike variations), both of which exclusively reflect parasympathetic modulation (vagal) [43][44][45].…”
Section: Heart Rate Variability (Hrv)mentioning
confidence: 99%
“…Although HRV is commonly analyzed using linear models, interest in nonlinear methods (symbolic analysis) has increased in recent years [43]. This methodology differs from standard approaches because it considers the qualitative properties of a single heart rate series [61].…”
Section: Comparison Of Hrv Between Groups and Different Agesmentioning
confidence: 99%
“…Although no cure exists for muscular dystrophy, current treatments aim to manage symptoms and improve quality of life. These treatments encompass physical therapy to maintain muscle strength and flexibility, medications to slow muscle degeneration, and sometimes surgery to correct deformities or relieve tight muscles (1)(2)(3)(4)(5)(6)(7). This patient education book offers a comprehensive overview of muscular dystrophy, covering its types, genetic factors, symptoms, diagnostic processes, and management and treatment options, all explained in simpler terms.…”
Section: Introductionmentioning
confidence: 99%